Study on Data Modeling and Collection in OSS Based on Hadoop - Lei Lei; Jingwen Li; Dapeng Gong; Rui Wang; Lei Su; Ningjiang Chen (Dianxin kexue)
According to the data acquisition and the modeling problem of telecom operators facing in the construction of EDC, the data status and data characteristics in the OSS was analyzed, a modeling method of hierarchical classification of combing theory and data model management idea were proposed, the unification of OSS data collection, sharing the modeling and data concentration were realized. Through the application of end to end analysis on mobile internet terminal as case subject,it provides reference for the construction on telecom industry EDC.